(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This research focuses on the creation of game design "Nareswari: The Adventure of Learning Sundanese Script," a two-dimensional platformer game designed to teach the Sundanese language’s characters. The main goal is to provide an interactive and engaging learning experience, enabling players to not only learn the Sundanese script but also to discover aspects of Sundanese culture and language. Qualitative research methods were used, with Teenagers as the primary subjects in their role as players. Data collection methods included in-depth interviews, participatory observation, and document analysis. Visual communication in games is crucial for effectiveness, with visual elements like characters, backgrounds, and interfaces capturing attention and imparting knowledge about Sundanese culture. The use of colors, shapes, and typography in visual elements helps create an effective learning environment conducive to knowledge acquisition. The game’s development followed the ADDIE model to improve learning quality. The analysis phase provided a thorough understanding of learning objectives, user needs, and game context, while the design was narrative-driven, focusing on character experiences. The ADDIE model provides a framework for the analysis, design, development, implementation and evaluation phases of the game Nareswari: The Adventure of Learning Sundanese Script.